2016
DOI: 10.1021/acsami.6b08866
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Synapses Based on in-Plane Gate Organic Electrochemical Transistors

Abstract: Realization of biological synapses using electronic devices is regarded as the basic building blocks for neuromorphic engineering and artificial neural network. With the advantages of biocompatibility, low cost, flexibility, and compatible with printing and roll-to-roll processes, the artificial synapse based on organic transistor is of great interest. In this paper, the artificial synapse simulation by ion-gel gated organic field-effect transistors (FETs) with poly(3-hexylthiophene) (P3HT) active channel is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 41 publications
1
145
0
Order By: Relevance
“…It should be noted here that short‐term synaptic plasticity can also be mimicked on ECTs with a relative low electrical field . Additionally, some ionotronic transistors exhibit both EDL and electrochemical operating mechanisms depending on the amplitudes of applied gate voltages . Thus, both short‐ and long‐term synaptic plasticity can be mimicked on such ionotronic transistors.…”
Section: Ionotronic Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted here that short‐term synaptic plasticity can also be mimicked on ECTs with a relative low electrical field . Additionally, some ionotronic transistors exhibit both EDL and electrochemical operating mechanisms depending on the amplitudes of applied gate voltages . Thus, both short‐ and long‐term synaptic plasticity can be mimicked on such ionotronic transistors.…”
Section: Ionotronic Transistorsmentioning
confidence: 99%
“…[14,35,[59][60][61] Additionally, some ionotronic transistors exhibit both EDL and electrochemical operating mechanisms depending on the amplitudes of applied gate voltages. [36,[62][63][64] Thus, both short-and long-term synaptic plasticity can be mimicked on such ionotronic transistors. For instance, Yu et al [32,48] reported chitosan-gated ITO transistors.…”
Section: Synaptic Plasticity Mimicked On Ionotronic Transistorsmentioning
confidence: 99%
“…[6] However, these algorithms have proven to be computationally intensive, requiring >100 graphics processing such as poly (3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), due to the low voltages required to modulate the material's conductance. [32][33][34][35][36] When implemented in a three-terminal architecture as an NVRM, PEDOT:PSS devices show exceptionally low switching energies (10 pJ for a 100 µm 2 device) in addition to linear and symmetric conductance response required for "blind" weight update (i.e., not involving a read). [32][33][34][35][36] When implemented in a three-terminal architecture as an NVRM, PEDOT:PSS devices show exceptionally low switching energies (10 pJ for a 100 µm 2 device) in addition to linear and symmetric conductance response required for "blind" weight update (i.e., not involving a read).…”
Section: Introductionmentioning
confidence: 99%
“…P3HT has great potential for use in organic electrochemical transistors (OECTs). Artificial synapses based on ion‐gel in‐plane gated OECTs have been obtained . Some important synaptic functions were emulated, including STP, PPF, self‐tuning, spike‐logic operation, spatiotemporal dendritic integration, and modulation.…”
Section: Three‐terminal Synaptic Devicementioning
confidence: 99%
“…Organic synapses Small 2019, 15,1900695 can be freestanding [41] and stretchable; [67] these are important advantages that give these synapses a wide range of applications in wearable, skin-attachable, and implantable electronics. Therefore, numerous organic electronic synapses have been fabricated based on many kinds of organic materials, including pentacene, [68,69] poly(3-hexylthiophene) (P3HT), [70,71] polymer poly(3,4-ethylenedioxythiophene) doped with poly(styrene sulfate) (PEDOT:PSS), [72,73] and PEDOT doped with poly(tetrahydrofuran) (PEDOT:PTHF). [74] P3HT has great potential for use in organic electrochemical transistors (OECTs).…”
Section: Organic Electronic Synapsesmentioning
confidence: 99%